Soybean-Extract and Cane Molasses for Active Dried Yeast Production - Ko Swan Djien; Oei Ping Jauw (Journal of Mathematical and Fundamental Sciences, 1964)
Abstract. Extract of germinating soybeans was used as enrichment in a medium of blackstrap cane molasses for producing active dried yeast. Optimum amount of soybeans and optimum germination time has been investigated. Yeast cells produced from a medium prepared from molasses, (NH4)2 SO4 and KH2PO4.Ichtisar. Ekstrak dari kedele berkatjambah telah dipakai untuk memperkaja perbenihan jang dibuat dari tetes untuk pembuatan ragi roti kering. Djumlah kedele dan waktu perketjambahan jang terbaik telah ditentukan. Ragi jang dibuat dari perbenikan tersebut mempunjai daja tahan lebih besar terhadap pengeringan daripada ragi jang dibuat dari perbenihan jang mengandung tetes, (NH4)2SG4 dan KH2PO4.